Interdependencies between monetary policy and foreign exchange intervention under inflation targeting: The case of Brazil and the Czech Republic - Jean-Yves Gnabo; Luiz de Mello; Diego Moccero (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The bulk of recent literature on foreign exchange interventions has overlooked the potential interdependencies that may exist between these operations and the conduct of monetary policy. This is the case even under inflation targeting and especially in emerging-market economies, because central banks often explicitly reserve the right to intervene to calm disorderly markets and to accumulate foreign reserves, and when the exchange rate is perceived as being out of step with fundamentals. This paper uses a friction model to estimate intervention reaction functions and the associated marginal effects for Brazil and the Czech Republic since the adoption of inflation targeting in these countries in 1999 and 1998, respectively.
Keywords: C24; E52; F31; 330; monetary policy; interventions; inflation targeting; friction model; Brazil; Czech Republic; Geldpolitik; Wechselkurspolitik; Inflation Targeting; Brasilien; Tschechische Republik